2021
DOI: 10.3390/ijerph18084031
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Foot Growth and Its Correlation with Anthropometric Parameters in a Representative Cohort of Schoolchildren from Southern Spain

Abstract: Background: The relationship between growth of the foot and other anthropometric parameters during body development until puberty has been scarcely studied. Some studies propose that growth of the foot in length may be an early index of puberty. The objective of this cross-sectional study was to analyze the relationship between the growth of the foot in length and width with other anthropometric parameters, in prepubertal and early pubertal schoolchildren (Tanner stage II). Methods: Using an instrument that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These data are not consistent with other studies carried out in schoolchildren in our country where it was observed that girls from 8 to 9 years old had a significantly worse footwear fit in length than boys [6]. Recent observational studies carried out in schoolchildren in southern Spain have shown that the age of onset pubertal foot growth was 7-8 years in girls and 8-9 years in boys and that, in the age range between 7 and 11 years, an adequate footwear fit in length is essential [3,5].…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…These data are not consistent with other studies carried out in schoolchildren in our country where it was observed that girls from 8 to 9 years old had a significantly worse footwear fit in length than boys [6]. Recent observational studies carried out in schoolchildren in southern Spain have shown that the age of onset pubertal foot growth was 7-8 years in girls and 8-9 years in boys and that, in the age range between 7 and 11 years, an adequate footwear fit in length is essential [3,5].…”
Section: Discussionmentioning
confidence: 76%
“…In general, an increase in HVA with age was also observed in both sexes, especially in girls in the age group between 11 and 14 years. We believe that this circumstance may be influenced in part by the increase in foot length and width that precedes the onset of Tanner's stage II in both sexes and that matches with the peak of longitudinal growth of the foot taking place prior to the peak of growth in height [2,3].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations